PENERAPAN METODE BAGHDADI DAN METODE TILAWATI DALAM MENINGKATKAN KEMAMPUAN TAHSIN AL-QUR’AN : Studi di Pondok Pesantren Nurul Hidayah Bani Rijah dan Pondok Pesantren Darul Mu’minin Nusantara Cilegon - Muhammad Muflih; Encep Syarifuddin; Hunainah; Siti Patimah; Kholid (QATHRUNÂ, 2025)
This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research location is in two Islamic boarding schools, namely the Nurul Hidayah Bani Rijah Islamic Boarding School (which applies the Baghdadi method) and the Darul Mu'minin Nusantara Cilegon Islamic Boarding School (which uses the Tilawati method). The respondents in this study consisted of 27 students, namely 15 students using the Baghdadi method and 12 students using the Tilawati method. The research subjects consist of pesantren leaders, ngaji teachers, and students. The results of the study show that 1) Baghdadi's method is effective in forming the basis of Qur'anic reading ability, especially in mastering the makharijul of letters and the introduction of basic reading structures through a drill approach. This method fosters the accuracy and accuracy of the pronunciation of the letters, although it tends to cause saturation if it is not varied. Meanwhile; 2) The Tilawati method has proven to be more effective in improving the fluency and beauty of reading (tartil), because it combines elements of rost songs and an interactive classical-individual approach. Students are more enthusiastic, active, and quick to master reading with a communicative and systematic approach; 3) The data obtained in the Tahsin Proficiency Level shows that the average tahsin ability of students with the Baghdadi method reaches a score of 79.8, while with the Tilawati method reaches 84.7. These results show that the Tilawati method is superior in building the ability to read the Qur'an as a whole, both in terms of makharijul lettering (accuracy of the sound of letters), tajweed (application of the law of reading), and waqaf (accuracy of stopping and continuing the reading). The conclusion of the study is that the improvement of the tahsin ability of the Qur'an does not only depend on the method used, but also on the quality of the teacher, the intensity of the exercise, and the supportive learning environment. It is hoped that the results of this research can be considered for Islamic educational institutions in developing an effective, dynamic, and consistent learning model of the Qur'an in accordance with the characteristics of students.